A copper-diffused layer on the surface of a NdFeB permanent magnet and a preparation method thereof
The copper seepage layer is prepared on the surface of the NdFeB permanent magnet through thermal diffusion and powder co-permeability, which solves the problems of unsolid adhesion of the copper plating layer, magnetic shielding and solution erosion in the prior art, and achieves high corrosion resistance and low magnetic properties Loss effect.
Patent Information
- Application Number
- CN202011475933.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-12-15
AI Technical Summary
The prior art has several problems when plating copper layers on the surface of NdFeB permanent magnets: 1) It is necessary to first plating a nickel layer, resulting in magnetic shielding; 2) Electroplating with aqueous or ionic solutions will cause erosion to the magnet; 3) Acid is required Pre-washing treatment may lead to acid etching and salting.
The copper seepage layer was prepared on the surface of the NdFeB permanent magnet by thermal diffusion method and powder co-penetration process. Cu6Sn5 alloy powder was used as the copper supply agent, ammonium chloride was used as the activator, and quartz sand was used as the inert medium. The heat diffusion was carried out through the co-penetration furnace. The treatment avoids the iron and copper replacement reaction during the electroplating process and the erosion of the magnet by solution.
The metallurgical combination between the copper seepage layer and the substrate is achieved, ensuring firm adhesion of the coating, excellent corrosion resistance and low magnetic performance losses, and avoiding the shielding effect of nickel plating on magnetic performance.
Smart Images

Figure CN114639540B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnetic material surface anticorrosion, and in particular to a copper infiltration layer on the surface of a NdFeB permanent magnet and a preparation method thereof. Background Art
[0002] At present, electroplating is still the most widely used surface protection method in the NdFeB permanent magnet material industry. This is mainly due to the stable process, low production cost, good corrosion resistance and decorative properties of the coating, which has been widely recognized by customers. Since the potential of NdFeB permanent magnet materials (about -0.70V) is much lower than the potential of metallic copper (+0.342V), the magnet will undergo a replacement reaction in an aqueous solution containing copper ions, and it is impossible to obtain a firmly attached copper layer on the surface of the permanent magnet by electrodeposition. Therefore, nickel plating is often used as the bottom layer, and then copper plating and other coatings are electroplated on its surface. For the above reasons, electroplated nickel-copper-nickel combined coatings are often used as protective coatings on the surface of NdFeB permanent magnets. However, metallic nickel has good magnetic conductivity, so nickel plating will reduce the magnetic properties of NdFeB materials, especially for magnets with a smaller volume or a thickness of less than 1mm, and nickel plating aqueous solution has a certain degree of corrosiveness to magnets. Since copper metal has no magnetic conductivity, the copper plating has little effect on the magnetic properties of NdFeB materials. Therefore, researchers have tried to directly infiltrate a copper layer on the surface of NdFeB magnets, and thus developed a technology for electro-infiltrating a copper layer in a CuCl-EMIC (1-ethyl-3-methylimidazole chloride) ion solution (see patent CN106591897 B); however, due to the high chemical activity of NdFeB permanent magnet materials and the structural morphology of the magnet surface (see Figure 1 ), the erosion of the magnet by the ionic solution during the plating process is also unavoidable. Therefore, there are still many problems that are difficult to solve when using this process to infiltrate the copper layer on the surface of the magnet.
[0003] If the hot melt plating method is adopted, the melting point of copper is 1083°C, which is close to the sintering temperature of the NdFeB magnet. Therefore, the existing technology cannot achieve the method of hot melt to cover the surface of the NdFeB magnet with a copper layer. Summary of the invention
[0004] In view of the above analysis, the present invention aims to provide a copper-plated layer on the surface of NdFeB permanent magnet and a preparation method thereof, which at least solves one of the following technical problems: (1) a nickel layer is plated before a copper layer is plated on the surface of NdFeB permanent magnet, which increases the process and causes magnetic shielding of the permanent magnet; (2) electroplating with aqueous solution or ionic solution erodes the NdFeB permanent magnet; (3) the permanent magnet surface must be pre-treated by pickling before being covered with a copper layer.
[0005] On the one hand, the present invention provides a copper-diffused layer on the surface of a NdFeB permanent magnet. The raw materials for preparing the layer include, by mass, 15-55 parts of a copper supply agent, 1.5-5.5 parts of an activator and 20-60 parts of an inert medium; the copper supply agent is Cu6Sn5 alloy powder.
[0006] Furthermore, the components in the NdFeB magnet are composed by mass percentage, including: 20.0-40.0% Pr-Nd, 0.5-3.0% Nd, 0.3-3.5% B, 0.2-5.5% Dy, 0.2-6.0% Tb, 0.1-3.8% Al, 0.1-2.0% Cu, and the rest is Fe.
[0007] Furthermore, the activator is ammonium chloride.
[0008] Furthermore, the inert medium is quartz sand.
[0009] Furthermore, the particle size of the Cu6Sn5 alloy powder is 100-150 mesh.
[0010] On the other hand, the present invention provides a method for preparing a copper-diffused layer on the surface of a NdFeB permanent magnet, which is used to prepare the copper-diffused layer on the surface of the NdFeB permanent magnet, comprising:
[0011] Step 1. Clean the surface of the NdFeB permanent magnet and dry it for later use;
[0012] Step 2. Place the copper supply agent, activator, inert medium and NdFeB permanent magnet into the co-infiltration furnace, evacuate the furnace, and fill it with inert gas;
[0013] Step 3. Turn the infiltration furnace, increase the temperature and maintain it;
[0014] Step 4: Cool down and stop rotating; exhaust gas and separate the surface copper-infiltrated NdFeB permanent magnet;
[0015] Step 5. Ultrasonic cleaning.
[0016] Furthermore, in step 3, the temperature is raised to 330° C. to 420° C.
[0017] Furthermore, in step 3, the temperature is maintained for 3 to 12 hours after heating.
[0018] Furthermore, in step 1, the cleaning treatment includes one or more of degreasing treatment, ultrasonic cleaning, and sandblasting treatment.
[0019] Furthermore, in step 1, the drying temperature is 60°C to 80°C.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] (1) The present invention uses a thermal diffusion method to prepare a copper-infiltrated layer on the surface of a NdFeB permanent magnet and forms a metallurgical bond with the substrate. Compared with the prior art, the present invention avoids the substitution reaction between iron and copper during the copper electroplating process, which causes the coating to be loosely adhered. The thermal diffusion layer between the coating and the substrate of the present invention ensures that the coating is firmly adhered to the surface of the substrate, and the coating has more excellent corrosion resistance.
[0022] (2) The present invention implements a powder co-infiltration process, which does not require pickling of the permanent magnet, thereby eliminating the corrosion of the magnet by the solution, and effectively avoiding the acid corrosion and salinization caused by pickling into the NdFeB permanent magnet, which further causes the copper to be loosely attached to the permanent magnet after copper plating.
[0023] (3) The copper co-diffusion protective layer prepared by the thermal diffusion method of the present invention has strong adhesion and excellent corrosion resistance, eliminates the nickel plating layer as the bottom layer, and can directly obtain a copper layer on the surface of the permanent magnet. The shielding effect of the prepared coating on the magnetic properties of the NdFeB material is greatly reduced, thereby being able to meet the quality requirements of electronic products for surface coatings.
[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0026] Figure 1 This is the microstructure morphology of NdFeB permanent magnet. DETAILED DESCRIPTION
[0027] In view of the problems existing in the art, such as the great influence of the surface nickel layer on the magnetic shielding of the NdFeB material and the inability to directly electro-infiltrate the copper layer in the solution, the present invention particularly adopts a thermal diffusion method to directly obtain a firmly attached copper layer on the surface of the magnet, thereby laying a good foundation for the surface coating. Based on the characteristics of the high activity and porous and loose surface of the NdFeB permanent magnet material prepared by the powder metallurgy method, the copper layer is directly prepared on the surface of the magnet by thermal diffusion technology, and the method of preparing the coating by the thermal diffusion method avoids the corrosion of the solution to the magnet. There is no edge effect caused by tip discharge during the process implementation. The coating and the substrate are metallurgically bonded, providing a bottom layer with strong bonding force and safer process execution.
[0028] The copper infiltration layer is directly prepared on the surface of the magnet using thermal diffusion technology, without the need for nickel plating as a pre-plating layer. This greatly reduces the impact of the nickel-based plating on the magnetic shielding of the NdFeB material, while solving the problem of solution corrosion of the substrate, effectively ensuring the adhesion and corrosion resistance of the surface protective coating.
[0029] The invention provides a copper-diffused layer on the surface of a NdFeB permanent magnet. The raw materials for preparing the layer include, by weight, 15-55 parts of a copper-supplying agent, 1.5-5.5 parts of an activator and 20-60 parts of an inert medium. The copper-supplying agent is Cu6Sn5 alloy powder.
[0030] Specifically, the components in the NdFeB permanent magnet are composed by mass percentage, including: 20.0-40.0% Pr-Nd, 0.5-3.0% Nd, 0.3-3.5% B, 0.2-5.5% Dy, 0.2-6.0% Tb, 0.1-3.8% Al, 0.1-2.0% Cu, and the rest is Fe.
[0031] Specifically, the activator is ammonium chloride, and the particle size is 100-150 mesh.
[0032] Ammonium chloride is thermally unstable. At the co-penetration temperature, ammonium chloride will slowly decompose to produce ammonia and hydrogen chloride gases. The produced hydrogen chloride and ammonia gases escape from the surface of the NdFeB permanent magnet, which can effectively prevent oxygen from approaching the NdFeB permanent magnet to form a dense metal oxide film to prevent co-penetration.
[0033] Specifically, the inert medium is quartz sand with a particle size of 60-100 meshes.
[0034] Inert medium can play a role of dispersion and buffering in the process of co-infiltration. Inert medium separates NdFeB permanent magnets from each other, and evenly disperses copper supply agent and activator in the inert medium. Through the uniform dispersion and thorough wrapping of NdFeB permanent magnets by inert medium, the copper supply agent and activator can fully contact and thoroughly wrap NdFeB permanent magnets, which plays an important role in uniform and sufficient co-infiltration. The main component of quartz sand is silicon dioxide. Silicon dioxide has extremely high thermal stability and chemical stability under non-alkaline conditions, and will not react with NdFeB permanent magnets and copper supply agent. Preferably, quartz sand is used as the inert medium.
[0035] Specifically, the particle size of the Cu6Sn5 alloy powder is 100-150 mesh.
[0036] Under high temperature conditions, NdFeB permanent magnets are prone to sintering and damage. The present invention uses Cu6Sn5 alloy as a copper supply agent to provide copper for the preparation of the copper infiltration layer, thereby avoiding damage to the NdFeB permanent magnets.
[0037] The present invention provides a method for preparing a copper-infiltrated layer on the surface of a NdFeB permanent magnet, comprising the following steps:
[0038] Step a. After cleaning the surface of the NdFeB permanent magnet, dry it at 60-80°C for standby use;
[0039] Step b. The copper alloy powder, ammonium chloride, and quartz sand are loaded into the co-penetration furnace, and finally the permanent magnet is loaded;
[0040] Step c. Close the infiltration furnace door, evacuate the chamber, and fill it with inert gas;
[0041] Step d. Turn on the rotating device and the infiltration furnace starts to rotate;
[0042] Step e. raising and maintaining the temperature in the infiltration furnace;
[0043] Step f. Stop heating, wait for the furnace temperature to drop to room temperature, and turn off the rotating device; open the exhaust valve, wait for the pressure in the furnace to drop to atmospheric pressure, open the furnace door, separate the charge, and take out the permanent magnet;
[0044] Step g. Ultrasonic cleaning of the permanent magnet to remove surface grit;
[0045] Specifically, the cleaning treatment includes one or more of degreasing treatment, ultrasonic treatment and sandblasting treatment, preferably includes multiple of degreasing treatment, ultrasonic treatment and sandblasting treatment, more preferably degreasing treatment, ultrasonic treatment and sandblasting treatment in sequence, specifically immersion in degreasing liquid and ultrasonic cleaning to remove surface oil stains; sandblasting to remove surface oxides.
[0046] Specifically, the inert gas in step c is one of N2 and Ar.
[0047] Specifically, in step d, the rotation speed of the co-infiltration furnace is 15-35 r / min.
[0048] The rotation speed of the co-infiltration furnace affects the contact time between materials. When the rotation speed is too fast (greater than 35r / min), the contact time of Cu6Sn5 alloy and NdFeB permanent magnet is too short, and it is impossible to fully contact and co-infiltration occurs; on the other hand, the rotation speed of the co-infiltration furnace is too slow (less than 15r / min), and the Cu6Sn5 alloy and NdFeB permanent magnet have too long contact time and melt mixing occurs, and the too slow rotation speed also affects production efficiency. Therefore, the rotation speed of the co-infiltration furnace in step d is set to 15-35r / min, at which the Cu6Sn5 alloy and NdFeB permanent magnet can fully contact and co-infiltration occurs, and no obvious melt mixing occurs.
[0049] Specifically, in step e, the furnace temperature is controlled at 330-420°C.
[0050] The melting point of Cu6Sn5 alloy is 415℃. At around 415℃, Cu6Sn5 alloy is about to melt. At this temperature, the copper atoms in the alloy will have a stronger mobility than solid copper atoms, and will migrate and move with the surface of NdFeB permanent magnets. At the same time, some neodymium atoms, iron atoms and boron atoms of NdFeB permanent magnets will also migrate and move into the copper infiltration layer. The atomic migration and movement of the interface of the two alloys realize the metallurgical bonding of the two alloys. At the same time, the preparation of the copper infiltration layer is a metallurgical bonding, not the traditional mixing of molten metals. Therefore, the temperature cannot be too high. To ensure the co-infiltration effect, the maximum temperature of the copper infiltration does not exceed 420℃.
[0051] Specifically, the insulation time in step e is 3-12h.
[0052] The holding time determines the duration of the co-infiltration. If the time is too short, the Cu6Sn5 alloy and the NdFeB permanent magnet will not have sufficient contact, resulting in incomplete and insufficient copper infiltration. If the time is too long, the production efficiency will decrease. Therefore, the holding temperature in step e is controlled to be 3-12h.
[0053] The temperature of the co-penetration treatment in step e of the present invention is 330-420° C., more preferably 350-400° C., more preferably 360-390° C. The time of the co-penetration treatment of the present invention is preferably 3-12 hours, more preferably 4-10 hours, more preferably 5-8 hours.
[0054] In order to meet the coating quality requirements of existing products such as electronic products for NdFeB permanent magnets, in a possible implementation scheme, nickel plating is performed after preparing the copper infiltration layer on the surface of the NdFeB permanent magnet, including:
[0055] Step h. Pre-treating the permanent magnet having the copper-plated surface layer obtained in step g;
[0056] Step i. Plating a nickel base layer on the surface of the permanent magnet having a pre-treated surface copper-plated layer to obtain a composite coating with the copper-plated layer as the bottom layer and the nickel-based plating layer on the surface.
[0057] Specifically, the pretreatment of the surface copper-infiltrated permanent magnet includes one or more of degreasing, pickling or activation.
[0058] Specifically, the nickel-plated base layer is a bright nickel-based plating layer.
[0059] Specifically, the copper infiltration layer has a thickness of 5.0-6.0 μm.
[0060] Specifically, the thickness of the bright nickel-based plating layer is 3.0-5.0 μm.
[0061] The equipment for the co-penetration treatment of the present invention is preferably a vacuum heating furnace, or a vacuum heating furnace with an atmosphere control function.
[0062] The experimental results show that the copper-infiltrated layer obtained by the technical method of the present invention can ensure that the NdFeB permanent magnet can withstand 1200 hours in a neutral salt spray atmosphere without red rust; the drawing test results show that the bonding force between the copper-infiltrated layer and the substrate is good; the magnetic property loss is less than 1%. It can be seen that the copper-infiltrated layer on the surface of the magnet by thermal diffusion has a small magnetic shielding effect, and the corrosion resistance and bonding force are enhanced.
[0063] The preferred embodiments of the present invention are described below to illustrate the principles of the present invention but are not intended to limit the scope of the present invention.
[0064] The following examples verify the corrosion resistance and evaluate the protective performance of the copper infiltration layer using a neutral salt spray test. The specific conditions are: 5wt% NaCl solution, pH 6.5-7.2, test temperature 35±2°C, sedimentation 1-2ml / 80cm 2 h. Use a pull-off test to test the bonding force between the surface coating and the substrate; test the loss of magnetic properties of the magnet before and after the coating is deposited, and evaluate the effect of the coating on magnetic shielding.
[0065] Embodiment 1
[0066] A copper-infiltrated coating on the surface of a NdFeB permanent magnet, wherein the raw materials for its preparation are calculated by weight:
[0067] Cu6Sn5 powder (100 mesh), 15.0 parts;
[0068] Ammonium chloride (100 mesh), 1.5 parts;
[0069] Quartz sand (80 mesh), 20.0 parts;
[0070] NdFeB permanent magnets 63.5 copies.
[0071] The method for preparing the copper-infiltrated layer on the surface of the NdFeB permanent magnet comprises the following steps:
[0072] Step a. After cleaning the surface of the NdFeB permanent magnet, dry it for standby use;
[0073] Step b. The Cu6Sn5 powder, ammonium chloride, and quartz sand are loaded into the co-penetration furnace, and finally the permanent magnet is loaded;
[0074] Step c. Close the infiltration furnace door, evacuate the chamber, and fill it with inert gas;
[0075] Step d. Turn on the rotating device and the infiltration furnace starts to rotate;
[0076] Step e. Wait until the temperature in the infiltration furnace rises to 360°C and keep warm for 3 hours;
[0077] Step f. Stop heating, wait for the furnace temperature to drop to room temperature, and turn off the rotating device; open the exhaust valve, wait for the pressure in the furnace to drop to atmospheric pressure, open the furnace door, separate the charge, and take out the permanent magnet;
[0078] Step g. Ultrasonic cleaning of the permanent magnet to remove surface grit;
[0079] Three samples were taken for testing, and the copper layer thickness was about 5-6μm. The neutral salt spray test lasted for more than 1200h, and no red rust, blistering or peeling appeared on the magnet surface; the minimum pulling force of the pull-out test was 11.3MPa; and the maximum magnetic loss was 0.3%.
[0080] Embodiment 2
[0081] A powder copper-infiltrated coating on the surface of a NdFeB permanent magnet, wherein the raw materials for its preparation are as follows by weight:
[0082] Cu6Sn5 powder (100 mesh), 25.0 parts;
[0083] Ammonium chloride (100 mesh), 3.5 parts;
[0084] Quartz sand (80 mesh), 30.0 parts;
[0085] NdFeB permanent magnets 41.5 copies.
[0086] The steps of preparing the copper infiltration layer on the surface of the NdFeB permanent magnet are as follows:
[0087] Step a. After cleaning the surface of the NdFeB permanent magnet, dry it for standby use;
[0088] Step b. The Cu6Sn5 powder, ammonium chloride, and quartz sand are loaded into the co-penetration furnace, and finally the permanent magnet is loaded;
[0089] Step c. Close the infiltration furnace door, evacuate the chamber, and fill it with inert gas;
[0090] Step d. Turn on the rotating device and the infiltration furnace starts to rotate;
[0091] Step e. Wait until the temperature in the infiltration furnace rises to 370°C and keep warm for 4 hours;
[0092] Step f. Stop heating, wait for the furnace temperature to drop to room temperature, and turn off the rotating device; open the exhaust valve, wait for the pressure in the furnace to drop to atmospheric pressure, open the furnace door, separate the charge, and take out the permanent magnet;
[0093] Step g. Ultrasonic cleaning of the permanent magnet to remove surface grit;
[0094] Three samples were taken for testing, and the copper layer thickness was about 5.2-6.2μm. The neutral salt spray test lasted for more than 1200h, and no red rust, blistering or peeling appeared on the magnet surface; the minimum pulling force of the pull-out test was 11.6MPa; and the maximum magnetic loss was 0.5%.
[0095] Embodiment 3
[0096] A powder copper-infiltrated coating on the surface of a NdFeB permanent magnet, wherein the raw materials for its preparation are as follows by weight:
[0097] Cu6Sn5 powder (100 mesh), 35.0 parts;
[0098] Ammonium chloride (100 mesh), 4.5 parts;
[0099] Quartz sand (SiO2, 80 mesh), 40.0 parts;
[0100] NdFeB permanent magnets 20.5 servings.
[0101] The steps of preparing the copper infiltration layer on the surface of the NdFeB permanent magnet are as follows:
[0102] Step a. After cleaning the surface of the NdFeB permanent magnet, dry it for standby use;
[0103] Step b. The Cu6Sn5 powder, ammonium chloride, and quartz sand are loaded into the co-penetration furnace, and finally the permanent magnet is loaded;
[0104] Step c. Close the infiltration furnace door, evacuate the chamber, and fill it with inert gas;
[0105] Step d. Turn on the rotating device and the infiltration furnace starts to rotate;
[0106] Step e. Wait until the temperature in the infiltration furnace rises to 370°C and keep warm for 5 hours;
[0107] Step f. Stop heating, wait for the furnace temperature to drop to room temperature, and turn off the rotating device; open the exhaust valve, wait for the pressure in the furnace to drop to atmospheric pressure, open the furnace door, separate the charge, and take out the permanent magnet;
[0108] Step g. Ultrasonic cleaning of the permanent magnet to remove surface grit;
[0109] Three samples were taken for testing, and the copper layer thickness was about 5.5-6.5μm. After 1200h of neutral salt spray test, no red rust, blistering or peeling appeared on the surface of the magnet; the minimum tensile force of the pull-out test was 11.8MPa; and the maximum magnetic loss was 0.6%.
[0110] Embodiment 4
[0111] A powder copper-infiltrated coating on the surface of a NdFeB permanent magnet, wherein the raw materials for its preparation are as follows by weight:
[0112] Cu6Sn5 powder (100 mesh), 45.0 parts;
[0113] Ammonium chloride (100 mesh), 5.5 parts;
[0114] Quartz sand (80 mesh), 30.0 parts;
[0115] NdFeB permanent magnets 19.5 servings.
[0116] The steps of preparing the copper infiltration layer on the surface of the NdFeB permanent magnet are as follows:
[0117] Step a. After cleaning the surface of the NdFeB permanent magnet, dry it for standby use;
[0118] Step b. The Cu6Sn5 powder, ammonium chloride, and quartz sand are loaded into the co-penetration furnace, and finally the permanent magnet is loaded;
[0119] Step c. Close the infiltration furnace door, evacuate the chamber, and fill it with inert gas;
[0120] Step d. Turn on the rotating device and the infiltration furnace starts to rotate;
[0121] Step e. Waiting for the temperature in the infiltration furnace to rise to 380°C and keeping it warm for 6 hours;
[0122] Step f. Stop heating, wait for the furnace temperature to drop to room temperature, and turn off the rotating device; open the exhaust valve, wait for the pressure in the furnace to drop to atmospheric pressure, open the furnace door, separate the charge, and take out the permanent magnet;
[0123] Step g. Ultrasonic cleaning of the permanent magnet to remove surface grit;
[0124] Three samples were taken for testing, and the copper layer thickness was about 5.8-6.9μm. After 1200h of neutral salt spray test, no red rust, blistering or peeling appeared on the magnet surface; the minimum pulling force of the pull-out test was 12.5MPa; and the maximum magnetic loss was 0.7%.
[0125] Embodiment 5
[0126] A powder copper-infiltrated coating on the surface of a NdFeB permanent magnet, wherein the raw materials for its preparation are as follows by weight:
[0127] Cu6Sn5 powder (100 mesh), 15.0 parts;
[0128] Ammonium chloride (100 mesh), 1.5 parts;
[0129] Quartz sand (80 mesh), 20.0 parts;
[0130] NdFeB permanent magnets 63.5 copies.
[0131] The copper infiltration and nickel plating composite coating on the surface of the NdFeB permanent magnet is prepared in the following steps:
[0132] Step a. After cleaning the surface of the NdFeB permanent magnet, dry it for standby use;
[0133] Step b. The Cu6Sn5 powder, ammonium chloride, and quartz sand are loaded into the co-penetration furnace, and finally the permanent magnet is loaded;
[0134] Step c. Close the infiltration furnace door, evacuate the chamber, and fill it with inert gas;
[0135] Step d. Turn on the rotating device and the infiltration furnace starts to rotate;
[0136] Step e. Waiting for the temperature in the infiltration furnace to rise to 390°C and keeping it warm for 8 hours;
[0137] Step f. Stop heating, wait for the furnace temperature to drop to room temperature, and turn off the rotating device; open the exhaust valve, wait for the pressure in the furnace to drop to atmospheric pressure, open the furnace door, separate the charge, and take out the permanent magnet;
[0138] Step g. Ultrasonic cleaning of the permanent magnet to remove surface grit;
[0139] Step h. Pre-treating the permanent magnet having the copper-infiltrated layer obtained in step g;
[0140] Step i. electroplating a nickel layer on the surface of the permanent magnet after pretreatment to obtain a combined coating of "copper infiltration layer + nickel layer".
[0141] Three samples were taken for testing, and the copper layer thickness was about 5.2-6.1μm, and the total thickness of the combined coating was about 10.3-12.7μm. The neutral salt spray test lasted for more than 1200h, and no red rust, blistering or peeling appeared on the surface of the magnet; the minimum tensile force of the pull-out test was 11.4MPa; and the maximum magnetic loss was 0.5%.
[0142] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A copper-infiltrated layer on the surface of a NdFeB permanent magnet, characterized in that: The raw materials for preparing the copper infiltration layer include, by mass, 15-55 parts of a copper supply agent, 1.5-5.5 parts of an activator and 20-60 parts of an inert medium; the copper supply agent is a Cu6Sn5 alloy powder; The copper infiltration layer is directly prepared on the surface of the magnet by using a thermal diffusion technology. The copper supply agent, activator, and inert medium are loaded into a co-infiltration furnace, and finally the permanent magnet is loaded to implement a powder co-infiltration process. The co-infiltration temperature is 330-420° C., the co-infiltration time is 3-12 hours, and the rotation speed of the co-infiltration furnace is 15-35 r / min. The Cu6Sn5 alloy and the NdFeB permanent magnet can fully contact and co-infiltration occurs, and no obvious melting and mixing occurs; The copper atoms in the Cu6Sn5 alloy powder undergo atomic migration and movement at the surface of the NdFeB permanent magnet, and at the same time, some of the neodymium atoms, iron atoms and boron atoms on the surface of the NdFeB permanent magnet also migrate and move, forming the copper infiltration layer at the interface between the two alloys; The copper infiltration layer has a thickness of 5.0-6.0 μm and is covered on the surface of the NdFeB permanent magnet by metallurgical bonding; The activator is ammonium chloride; The inert medium is quartz sand.
2. The copper-infiltrated layer on the surface of the NdFeB permanent magnet according to claim 1, characterized in that: The components in the NdFeB permanent magnet include, by mass percentage, 20.0-40.0% Pr-Nd, 0.5-3.0% Nd, 0.3-3.5% B, 0.2-5.5% Dy, 0.2-6.0% Tb, 0.1-3.8% Al, 0.1-2.0% Cu, and the rest is Fe.
3. The copper-diffused layer on the surface of the NdFeB permanent magnet according to claim 1, characterized in that: The particle size of the Cu6Sn5 alloy powder is 100-150 meshes.
4. A method for preparing a copper-infiltrated layer on the surface of a NdFeB permanent magnet, characterized in that: The method for preparing the copper-diffused layer on the surface of the NdFeB permanent magnet according to any one of claims 1 to 3 comprises: Step 1. Clean the surface of the NdFeB permanent magnet and dry it for standby use. The cleaning process includes one or more of degreasing, ultrasonic cleaning, and sandblasting. Step 2. Place the copper supply agent, activator, inert medium and NdFeB permanent magnet into the co-infiltration furnace, evacuate the furnace, and fill it with inert gas; Step 3. Turn the infiltration furnace, raise the temperature to 330-420°C, and maintain it for 3-12 hours. The speed of the infiltration furnace is set to 15-35r / min; Step 4: Cool down and stop rotating; exhaust gas and separate the surface copper-infiltrated NdFeB permanent magnet; Step 5. Ultrasonic cleaning.
5. The method for preparing the copper-diffused layer on the surface of the NdFeB permanent magnet according to claim 4, characterized in that: In the step 1, the cleaning process includes degreasing, ultrasonic cleaning and sandblasting.
6. The method for preparing the copper-diffused layer on the surface of the NdFeB permanent magnet according to claim 4, characterized in that: In the step 1, the drying temperature is 60°C to 80°C.
Citation Information
Patent Citations
A cyanide-free ionic liquid copper plating solution and copper plating process
CN106591897B
Corrosion-resistant sintered NdFeB magnet modified through copper-tin crystal boundary and preparing process thereof
CN103996477A
Preparation method for vacuum mechanical energy aided diffusing zinc-aluminum-chromium alloy layer
CN107058942A
Neodymium iron boron magnet permeated by heavy rare earth and method for permeating heavy rate earth on surface of neodymium iron boron magnet
CN108039259A
Surface-alloyed high-corrosion-resistance sintered NdFeB magnet and preparation method thereof
CN110993231A